Enhancing Children's Language Skills Through Storytelling Method with Audio-Visual Media - Nur Asifudin; Nazla Maharani Umaya; Sudaryono Sudaryono (CV. Publikasi Indonesia, 2025)
Early childhood education is an important period in language development, which is one of the fundamental aspects in the formation of communication and interaction of children. This study aims to improve the language skills of children aged 5-6 years through the storytelling method with audio-visual media. The research used the literature study method by collecting data from various related scientific journals. The results showed that the storytelling method using audio visual media can significantly improve children's language skills, both in the aspects of listening, speaking, reading, and writing. Audio-visual media attracts children's attention, makes the learning process more fun, and provides interactive experiences that motivate children to actively participate. The conclusion of this study is that the storytelling method using audio visual media is an effective learning approach in developing early childhood language skills.